The Influence of Accounting Knowledge and Experience Entrepreneurship Towards Business Success: Case Study on MSMEs in Telukjambe Timur District, Karawang Regency - Mowa, Beatrix; Sujaya, Fista Apriani; Astriani, Devi (Westscience Press, 2025)
This research was carried out to analyze Accounting Knowledge and Entrepreneurial Experience on Business Success in East Telukjambe District, Karawang Regency. It is implemented in MSME managers in East Telukjambe District. By using primary data obtained through the process of distributing questionnaires to respondents. The population in this study is MSMEs in East Telukjambe District. The sampling technique used was simple random sampling with the results of 93 respondents. The tool for data analysis used is the IBM SPSS Software V 21, with the results of the analysis of accounting knowledge variables and the variability of experience in authority have a positive influence on business success. The impact of the results of this study can be used to contribute knowledge to MSMEs in East Telukjambe District about business success by taking into account accounting knowledge and entrepreneurial experience.